Zenab k.jabar NUMERICAL SOLUTIONS OF THE GENERALIZED BURGERS HUXLEY EQUATION BY FINITE DIFFERENCE METHOD - Jabar, Zenab (University of Thi-Qar Journal of Science, 2019)
In this paper, numerical solutions of the generalized Burgers-Huxley equation are obtained by using explicit finite difference method and Crank- Nicalson(C.N) finite difference method. we compare our result with the exact solution ,our Numerical results show that C.N finite difference method is more efficient and more accurate than the explicit finite difference method when the value of δ is small.